“SAKSHAM”: A Government Process Reengineered Model for Scholarship and Feereimbursement and its Impact on Society (A study of Uttar Pradesh, the most populous state of India) - Gupta, Dr. Saurabh; Rajan, Sameer (IJRDO- Journal of Educational Research, 2017)
Government executes various schemes to uplift the weaker section of the society. Scholarshipdisbursement and Fee reimbursement is one of the major schemes which assure that money is nota constraint for credible students aspiring for higher studies and professional courses. Thescheme also assures the upliftment of downtrodden students and put them in main stream ofsociety. SAKSHAM-eScholarship portal is the concept of electronic transfer of scholarship andfee reimbursements to the students directly into their bank accounts which enables andempowers students of weaker section of the society with education. This paper explores thevarious aspects of Government Process Reengineering Model “SAKSHAM” which has beenadopted by the Government to interact, interface and transact with all the concerned stakeholdersin a integrated and interoperable manner for disbursement of scholarship and fee reimbursementin transparent, time bound, effective and efficient manner, directly into the bank account ofdowntrodden students. The objective of the project is not to generate revenue however it saves alot of revenue indirectly by minimizing the leakage of funds.